PERANAN KANTOR URUSAN AGAMA (KUA) DALAM MENGURANGI PERCERAIAN - Husin, Taufik Nur; Syamsuddin, S; Abdullah, Mu'in (AL HUKMU: Journal of Islamic Law and Economics, 2025)
Marriage in Islam is a sacred bond between a man and a woman to build a happy family in this world and the hereafter. However, various issues such as conflict, economic problems, and poor communication often trigger divorce. Islam permits talaq as a last resort, although it is highly discouraged. Amid the high divorce rates, the role of the Office of Religious Affairs (KUA) becomes crucial—not only as a marriage registrar but also as a guide for prospective brides and grooms. Through premarital counseling, couples are provided with religious knowledge, household skills, and conflict resolution strategies. Unfortunately, many people are still unaware of the importance of this course. The low awareness is due to limited religious literacy and apathy towards family development. In fact, effective premarital courses can prevent divorce. Therefore, strengthening the role of the KUA and increasing public education are essential to create families that are sakinah, mawaddah, and rahmah.